Shape optimization of soft magnetic composite inserts for electromagnetic stirrer with traveling magnetic field. Issue 1 (2nd January 2020) - Bolotin, Kirill; Shvidkii, Evgeniy Leonidovich; Sokolov, Igor; Bychkov, Sergey Alekseevich
Abstract : Purpose: The purpose of this paper is to search optimal shape of soft magnetic composite-based inserts used to compensate the working gap between the liquid metal and the induction stirrer in metallurgical installations. Design/methodology/approach: The study was based on numerical simulation of electromagnetic processes in frequency domain. To optimize inserts shape, the Nelder–Mead method was used. The maximum of integral electrodynamic force along x -axis was chosen as the objective function. All simulations were performed in finite element software package Comsol Multiphysics. Findings: Optimal inserts shape was determined, at which the value of integral electrodynamic force along x -axis increased by 20% from 692 to 792 N. Originality/value: Magnetic concentrators based on soft magnetic composite materials have long been used in high-frequency systems; at the same time, their use in low-frequency systems has not been previously considered in detail. The study of the shape effect of concentrators on the effectiveness of electromagnetic field in a liquid metal in a three-dimensional formulation was carried out for the first time.